Eliciting Public Preferences For Managing Cultural Heritage Sites: Evidence from a Case study on the Temples Of Paestum - Patrizia Riganti; Annamaria Nese; Ugo Colombino (European Regional Science Association (ERSA), 2004)
This paper discusses ways of improving the management of cultural heritage sites and cities, focusing on new forms of involvement and public participation based on public preferences' elicitation. The problem of city governance and of the appropriate level of democratic participation needs an integrated approach, capable of bridging the practice of urban design, conservation of the built environment and decision-making support system. This paper reports results from a survey using conjoint choice approach questions to elicit people's preferences for cultural heritage management strategies for an outstanding world heritage site: the Temples of Paestum, in Italy. The potential of the above-mentioned methodologies' within the current cultural heritage research scenario is also discussed.
Keywords: 330